Searching on campus? The marriage market effects of changing student sex ratios - Nico Pestel (Review of Economics of the Household, 2021)
This paper studies how secular changes in the student sex ratio affect marriage market outcomes for university graduates. Using data from Germany, I find that a higher own-gender share within the field of study reduces marriage market opportunities for women, while the opposite is true for men. Moreover, an imbalanced student sex ratio changes the composition of couples. For women, a higher female share decreases the probability of having a spouse from the same field, while men are more likely to marry down with respect to educational status when the male share is high. These findings suggest that the secular changes in the sex ratio of university students have important implications beyond the labor market by affecting the household composition among the high-skilled population.
Keywords: 330; D10; I23; I24; J12; Marriage markets; Sex ratio; Higher education; Germany